Factors associated with full immunization coverage among under-2 years children in Nepal - Thapa, Salina; Chaudhary, Pramodh; Sangroula, Raj Kumar; Shrestha, Arati Dhoju; Balampaki, Pabitra Balampaki; Thapa, Janak Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: Immunization is a cost-effective intervention; countries committed to improving child health and well-being by 2030 and assessing overall progress towards the sustainable development goals are required to reduce vaccine-preventable illness and deaths, which profoundly rely on immunization. Methods: Cross-sectional study was carried out in Nepal using secondary data from the Nepal Demographic and Health Survey 2016 to fulfil the objective and find out the factors associated with full immunization coverage among under two years children in Nepal. This study was conducted in 21 districts based on a low human development index. Results: Among the 306 respondents, this study found that full immunization coverage was (42.2%) and male respondents 51 % were more vaccinated as compared to female 49% of respondents. Similarly, there were mother occupations statistically associated with full immunization coverage. Instructional deliveries (51.7%) were not statistically associated with full immunization coverage. Agriculture and services were 1.6 times more likely to be immunized as compared to not working women [OR 1.6 (0.99-2.56)]. Child age was statically associated with full immunization and children aged 12-23 months were 39 (19.51-79.17) and 24 (17.99-64.23). Conclusions: Immunization is the most cost-effective and universal public health weapon. The overall full basic immunization coverage was still lower than the global target. BCG coverage was high; however, only half of the respondents received the second dose of measles. Complete basic immunization was significantly associated with child age, child sex, and mother’s occupation.